Strategi Promosi Dalam Meningkatkan Daya Saing Pemasaran Catering Pada Budhe Jaya Catering - Meri Mayang Sari; Eduard Hotman Purba; Ramadhan Aulia Sasmito; Melissa Rizka Aulia (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
This research aims to determine promotional strategies in increasing the competitiveness of catering purchases at Budhe Jaya Catering. The data used is primary data obtained directly from the research location in the form of the type of advertising used and secondary data in the form of a brief history of Budhe Jaya Catering. The analytical method used in this research is qualitative analysis. Based on the research conducted, the data obtained shows that the promotion carried out by Budhe Jaya Catering was not successful because it only used brochures and signboards, this greatly af ected the level of orders and income of Budhe Jaya Catering to increase purchasing competitiveness. Therefore, it would be better for Budhe Jaya Catering to use more ef ective media in carrying out its promotions so that the public can know about the existence of Budhe Jaya Catering so that the level of orders increases.